National survey of the management of Diabetic Ketoacidosis (DKA) in the UK in 2014. Issue 2 (8th October 2015) - Dhatariya, K. K.; Nunney, I.; Higgins, K.; Sampson, M. J.; Iceton, G.
Abstract: Aim: To examine, in a national survey, the outcomes of adult patients presenting with DKA in 2014, mapped against accepted UK national guidance. Methods: Data were collected in a standardized form covering clinical and biochemical outcomes, risk and discharge planning. The form was sent to all UK diabetes specialist teams ( n = 220). Anonymized data were collected on five consecutive patients admitted with DKA between 1 May 2014 and 30 November 2014. Results: A total of 283 forms were received ( n = 281 patients) from 72 hospitals, of which 71.4% used the national guidelines. The results showed that 7.8% of cases occurred in existing inpatients, 6.1% of admissions were newly diagnosed diabetes and 33.7% of patients had had at least one episode of DKA in the preceding year. The median times to starting 0.9% sodium chloride and intravenous insulin were 41.5 and 60 min, respectively. The median time to resolution was 18.7 h and the median length of hospital stay was 2.6 days. Significant adverse biochemical outcomes occurred, with 27.6% of patients developing hypoglycaemia and 55% reported as having hypokalaemia. There were also significant issues with care processes. Initial nurse‐led observations were carried out well, but subsequent patient monitoring remained suboptimal. Most patients were not seen by a member of the diabetes specialist team during the first 6 h, but 95% were seen before discharge. A significant minority of discharge letters to primary care did not contain necessary information. Conclusion: Despite widespread adoption of national guidance, several areas of management of DKA are suboptimal, being associated with avoidable biochemical and clinical risk. What's new?: In 2013, a revised version of national guidance on the management of DKA was published, but there are no data to show that these recommendations actually work. This is the largest national survey on the management of DKA. Most patients developed hypokalaemia and >25% developed hypoglycaemia. There were also significant issues with care processes. The management of DKA will need to change to prevent hypokalaemia but this will necessitate a shift in the location in which patients are treated. As a result of moving to a high‐dependency or intensive care environment, however, care processes may improve.